Growth Performance of Different Provinces of Azadirachta Indica - Bisaria, A. K.; Tyagi, Shiv Ram; Ahanger, Mohammad Abass (Indian Forester, 2014)
Neem ( Azadirachta indica ) is a multipurpose tree which has been found as core species for desert afforestation in India because it is adapted to tropical and subtropical climates and can tolerate high summer temperatures even up to 50 °C. Present study was conducted on eighteen months old saplings of Azadirachta indica procured from different provinces of India and planted in Tapovan, Gwalior in September, 2000. Growth performance viz., plant height, plant girth, flowering percentage and percentage of plant establishment of different saplings has been studied after ten years of initial plantation. Maximum plant height (6.610±0.260 m) has been attained by saplings of Kurnool (A.P.) whereas saplings of Nagpur (Maharashtra) were found to possess maximum plant girth (0.378±0.007 m) after ten years of initial plantation. Better flowering percentage (86.95%) was shown by saplings procured from Hisar (Haryana). After ten years of plantation, saplings of Bhilwara (Rajasthan) have been found with 100% plant establishment percentage and can be considered as better adapted provinces to Tapovan, Gwalior.